Cis-regulatory elements and chromatin structure: role in zebrafish six3a/six2a gene expression. - Gómez Marín, Carlos; Gómez Skarmeta, José Luis (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2013)
Six3 and Six2 are transcription factors from the SIX family of homeoproteins. The Six genes play important roles during development controlling patterning, cell proliferation and migration. Across bilaterian evolution, Six3 and Six2 genes have been maintained in very close proximity in the genome despite displaying largely different expression patterns. This suggests that these genes are exposed to different regulatory environments. Using zebrafish as a model, we are trying to precisely define the regulatory landscape for each gene and determine how and why synteny is maintained and differential expression patterns is generated. For this goal, we use our zebrafish histone epigenomic data (Rada-Iglesias, 2011) to select and test putative enhancers (Bessa et al., 2009) for both genes. We also use chromatin conformation capture (3C) derived technologies (Splinter et al., 2011) to elucidate the global chromatin architecture of each promoter. In addition, BAC recombineering will allow us to test the influence of regulatory elements and potential insulators on gene expression and chromatin architecture of the locus. In this presentation I will talk about the theoretical context of the project, methodological set up and work in progress. Alvaro Rada-Iglesias, Ruchi Bajpai, Tomek Swigut, Samantha A. Brugmann, Ryan A. Flynn & Joanna Wysocka. “A unique chromatin signature uncovers early developmental enhancers in humans”. Nature, 2011 Feb 10;470(7333):279-83 Jose Bessa, Juan J. Tena, Elisa de la Calle-Mustienes, Ana Fernandez-Miñan, Silvia Naranjo, Almudena Fernández, Lluis Montoliu, Altuna Akalin, Boris Lenhard, Fernando Casares,and Jose Luis Gomez-Skarmeta. “Zebrafish enhancer detection (ZED) vector: a new tool to facilitate transgenesis and the functional analysis of cis-regulatory regions in zebrafish”. Dev Dyn, 2009 Sep;238(9):2409-17. Erik Splinter, Elzo de Wit, Elphège P. Nora, et al. “The inactive X chromosome adopts a unique three-dimensional conformation that is dependent on Xist RNA”. Genes DeV 2011 Jul 1;25(13):1371-83